Study of animal welfare status and heat stress measures applied in dairy cow herds in Hungary - Gudaj, Richárd; Komlósi, István; Brydl, Endre (Acta Agraria Debreceniensis, 2010)
The following material focuses on dairy production and climate related issues in Hungary. All the data was gathered during PhD project: Study of animal welfare status in dairy cow herds in Hungary. Relations between animal welfare and climate changes expressed by increase in temperature are described. Extremely hot weather creates hard conditions for milking cows when animal welfare is highly compromised. From the preliminary results obtained one might formulate hypothesis that there are still areas on the farms where immediate actions should be taken to give a relief to cows in hot seasons. There was found significant number of farms with too many animals per one water trough, dirty water troughs, limited access to water troughs and hazardous surface for cows in critical places where many animals are gathered. Calves with not sufficient amount of water in hot days and other parts of the year were reported. Silage exposure to the sun and mouldy food in a silage clump was also found to be an important factor in monitoring impact of warm weather. Half of the farms letting animals to spend time on the pasture or paddock did not provide shade for animals. Low conception rate of first insemination was predicted to be influenced by heat stress, what is proved by lack of heat decreasing measures taken on the farms.